Feasibility of a Conditional Knockout System for Chlamydia Based on CRISPR Interference - Ouellette, Scot P. (Frontiers in Cellular and Infection Microbiology, 2018)
Chlamydia is an obligate intracellular bacterium and, as such, has significantly reduced its genome size and content. Although recent advances have allowed for transformation of C. trachomatis with an exogenous plasmid, genetic manipulation of Chlamydia remains challenging. In particular, the ability to create conditional knockouts has not been developed. This is particularly important given the likelihood that most genes within the small genome of Chlamydia may be essential. Here, I describe the feasibility of using CRISPR interference (CRISPRi) based on the catalytically inactive Cas9 variant (dCas9) of Staphylococcus aureus to inducibly, and reversibly, repress gene expression in C. trachomatis. CRISPRi has been developed and used successfully in a variety of bacterial organisms including E. coli and Mycobacterium tuberculosis. I first describe the creation of a single plasmid system for CRISPRi in Chlamydia, targeted to a non-essential gene, incA, that expresses a dispensable inclusion membrane protein. Control transformations of C. trachomatis serovar L2 with plasmids encoding only the dCas9, under the control of an inducible promoter, or only the guide RNA (gRNA) targeted to the 5' UTR of incA, expressed constitutively, failed to prevent expression of IncA. Importantly, expression of dCas9 alone did not have a deleterious effect on chlamydiae. Transformation of C. trachomatis with a plasmid combining the dCas9 and a gRNA targeting incA and induction of expression of the dCas9 resulted in the reversible inhibition of IncA expression. Consequently, conditional knockout mediated by CRISPRi is feasible in Chlamydia. Potential improvements and experimental concerns in using the system are also discussed.